Investigasi Sifat Kepadatan dan Daya Dukung Bahan RAP(Reclaimed Asphalt Pavement) Bergradasi DBM (Dense Bitumen Macadam) - Fitriyanto, Ragil; , Ir. Sri Sunarjono<M.T., PH.D; , Senja Rum Harnaeni,ST.M.T (2016)
The hardening road is a common being used in Indonesia, because easy to get, efficiency and comfort for all the user of transportations, so that way is really needed a good planning to create a road. In this case, a harden road has been designed in particular planning, so with particular planning that had been predicted so in particular time hardening road will have broken. A broken of the harden road is called RAP ( Reclaimed Asphalt Pavement). The using of RAP is one of solution to overcome road problem. The goal of this research is to recycle material of asphalt and to know the density point and the support power RAP material new aggregate with same gradation. This research is used laboratories test method. Materials that has been used is RAP materials that had been coming from PANTURA Tegal Central Java. In this research has had several testing of RAP materials and new aggregate that namely filtering gradation, mass, aberattion test. Than the researcher make thing of RAP materials and new aggregate with using DBM gradation for proctor density, the test is used proctor standard and modified proctor. From this research the optimum degree of water and maximum weigh of dry content from modified proctor standard and modified proctor has been used to make CBR testhing, from CBR testing has been got the materials support point. Base on analysis of the density character and the support power RAP materials with DBM gradation has been got the test result of density. It can be concluded that the point of new aggregate materials is higher than RAP materials, this is because the masss, type of gradation and the form of granule materials that has been used. The result point of a support power test has been got the data that new aggregate having support power higher than RAP, this is because being influenced by the point of density that has been higher than RAP. The result of standard proctor test, the density maximum RAP is 1,47 gr/cm3, the degree of optimum water 7,7 % and new aggregate is 1,83 gr/cm3, new optimum of water 8,9 %. The result of modified proctor test of RAP maximum is 1,57 gr/cm3, the degree of optimum water 7,1 % and new aggregate is 1,92 gr/cm3, the degree of optimum water 8,4 % the density of modified proctor tests that has been used to look for the degree water of CBR. The result of CBR RAP test has been got 57,78 % meanwhile the result of new aggregate test is 92,44 %. From the result of the research can be concluded that RAP and new aggregate gradation with DBM , the point of new aggregate is totally higher than the result of RAP.